2001
DOI: 10.1097/00002030-200108170-00011
|View full text |Cite
|
Sign up to set email alerts
|

A menstrual cycle pattern for cytokine levels exists in HIV-positive women: implication for HIV vaginal and plasma shedding

Abstract: We provide evidence of elevated vaginal cytokine levels during menses, which appear to regulate vaginal and not plasma HIV shedding, suggesting that a menstrual cycle pattern exists for cytokine production in HIV-positive women impacting vaginal shedding of HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 24 publications
5
48
2
3
Order By: Relevance
“…This association has not been previously reported, although one study reported that a positive Candida culture was associated with vaginal IL-8 during menses (Al-Harthi et al, 2001). The current study also found a negative relationship between lactobacilli and IL-8.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This association has not been previously reported, although one study reported that a positive Candida culture was associated with vaginal IL-8 during menses (Al-Harthi et al, 2001). The current study also found a negative relationship between lactobacilli and IL-8.…”
Section: Introductionsupporting
confidence: 56%
“…For example, high vaginal IL-8 concentrations were associated also with amniotic fluid infections in women with preterm labor (Hitti et al, 2001) and in women with bacterial vaginosis (Spandorfer et al, 2001;Wennerholm et al, 1998). Vaginal IL-8 increases were noted also after sexual activity, after exposure to some microbicides and during menses (Al-Harthi et al, 2001;Fichorova, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is the first to report on the measurement of cervicovaginal cytokine levels to assess urogenital irritation in response to vaginal products in a clinical safety study. Cytokines regulate mucosal immune responses and, in the vaginal environment, may play a critical role in the pathogenesis of HIV-1 and other STIs [17]. N-9-induced vaginal inflammation has been linked to increased HIV activity via IL-1-mediated mechanisms [18].…”
Section: Discussionmentioning
confidence: 99%
“…20 Secretion of mannosebinding lectin, a molecule in the complement system that plays a critical role in host protection, from vaginal epithelial cells is increased in the LUT phase of the menstrual cycle. 49 Other investigations found that CV immune mediators did not change based on the menstrual cycle (e.g., IL-10, TNF-a, IL-8, RANTES, and TNFR II), 19,26,50 but were higher during menstruation. 26,50 Genital tract cytokines have also been shown to vary based on clinical factors, such as cervical ectopy, inflammation, and sexual activity.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 98%
“…18 However, there is a paucity of data regarding the effect of the menstrual cycle on immune cell recruitment and activation in the lower reproductive tract, including the ectocervix and vagina, 19,20 with some studies showing no changes in CD4 and CCR5-positive cells, based on the menstrual cycle, in ectocervical explants. 21 Previous studies regarding the effect of endogenous hormones on mucosal HIV targets in the lower genital tract have been done primarily with explants obtained from women undergoing elective surgeries such as hysterectomies [21][22][23][24][25] or among small cohorts of women in a longitudinal 19,[26][27][28] or cross-sectional design. 29 While surgical explants offer convenience and supply tissue without invasive biopsy procedures, women undergoing indicated surgery invariably have a host of medical comorbidities and concomitant medication use, which may affect study endpoints.…”
Section: Introductionmentioning
confidence: 99%